AB0243 Serum levels of angiogenic and proinflammatory cytokines to discriminate between 6 sets of remission criteria in ra. (15th June 2017) - Ramírez, J García; Cuervo, A; Celis, R; Ruiz-Esquide, V; Hernández, MV; Sanmartí, R; Cañete, JD
Abstract : Background: The ideal definition of remission in RA remains to be agreed. Angiogenic factors and proinflammatory cytokines are key in RA pathogenesis. Objectives: The aim of this study was to analyse serum levels differences of angiogenic and inflammatory biomarkers between SDAI, CDAI, ACR, DAS28 and sonographic remission in patients with (RA). Methods: We selected patients with RA in clinical remission (DAS28-ESR<2.6 for >6 months). PDUS of knees and hands was performed. Serum levels of biomarkers of inflammation/angiogenesis were determined by Quantibody® Human Array. Patients were classified according to 6 sets of remission criteria: SDAI (<3.3), CDAI (<2.8), ACR, DAS28-ESR (<2.6), Doppler (score Doppler=0) and UdAS (ultrasound defined active synovitis:no joints with SH≥2+PD) Results: 60 patients with RA were collected. 76% female, aged (mean) 53 years; disease duration 110 months. 47 (76%) csDMARDs, and 27 (45%) biological therapies. At baseline, 67% of patients had PD signal and 48% fulfilled criteria for previously defined UdAS. Although patients in sonographic remission had lower levels of inflammatory biomarkers such as IL-6, IL-17 or IL-23, no significant differences were found between the 6 sets of remission criteria. Angiogenic biomarkers such as CXCL6 (0.039), ENA78 (0.007), SDF1 (0.047) and VEGF-R1 (0.025) were significantly lower in patients fulfilling CDAI remission. Patients with no PD signal (0.009) and no UdAS (0.006) had significantly lower levels of bFGF. Conclusions: RA patients in CDAI remission had significantly-lower levels of angiogenic cytokines. However, no differences in serum levels of proinflammatory cytokines were found between the 6 sets of remission criteria. Disclosure of Interest: None declared